News consumption, political preferences, and accurate views on inflation - David-Jan Jansen; Matthias Neuenkirch (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2017)
Using three waves of a customised survey among Dutch households, this paper studies the variation in people's views on inflation. Based on a range of panel regressions, we find that accurate perceptions of recent price changes are an important determinant of the accuracy of next-year inflation expectations. The realism of inflation perceptions is, in turn, related to the intensity of newspaper consumption and also affected by the broadness of a person's political preferences. However, more frequent newspaper usage does not necessarily reduce errors in inflation perceptions.
Keywords: D12; D83; D84; E31; E58; 330; inflation expectations; inflation perceptions; newspaper readership; politicalpreferences; household survey data